Analysis Of Implementation of Teamwork Domains in the Application of Interprofessional Education : at Polytechnic of Ministry of Health Surakarta - Rachmat, Nur; Agustina, Lusinta (Advances in Social Sciences Research Journal, 2020)
Purpose: The purpose of this study is to analyze the implementation of teamwork in the application of Interprofessional Education so that and to identify the supporting factors and inhibiting factors. Method: This research methodology using the mixed method. The participants of this study were 200 students consisting of 2 majors namely midwifery and herbal majors at the Polytechnic of the Ministry of Health Surakarta. Participants are taken from students who have entered semester 3 in each study program. This research was conducted during February to August 2019. The specification of this research is descriptive analysis which aims to make a description of the facts, the characteristics and the relationship of the phenomenon. Data was collected through observation and interviews and then analyzed using thematic analysis. Results: team work in the midwifery department was quite good at 40.8%, and the herbal medicine department was quite good at 46.2%. Each department meets indicators of successful Interprofessional Education, which is able to resolve conflicts within the team openly. Conclusion: Team collaboration in the implementation of Interprofessional Education has been going well, the supporting factor to give the highest contribution is open conflict, The factor which is the highest obstacle is the factor of disagreement regarding the allocation of resources within the team.